2017
DOI: 10.7554/elife.25887
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota regulates visceral pain in the mouse

Abstract: The perception of visceral pain is a complex process involving the spinal cord and higher order brain structures. Increasing evidence implicates the gut microbiota as a key regulator of brain and behavior, yet it remains to be determined if gut bacteria play a role in visceral sensitivity. We used germ-free mice (GF) to assess visceral sensitivity, spinal cord gene expression and pain-related brain structures. GF mice displayed visceral hypersensitivity accompanied by increases in Toll-like receptor and cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 79 publications
1
81
2
2
Order By: Relevance
“…Most convincingly, converging evidence from GF mice indicates that the amygdala transcriptome is hyperactive in the absence of a microbiota. [36,37] This hyperactive state is consistent with the altered phenotype of GF mice in regards to both social and fearrelated behaviors, [101,110] pain sensitivity, [119] as well as elevated stress-induced HPA axis responses (see Figure 4). [8,10] More broadly, the studies outlined below suggest that microbiota-toamygdala signalling may result in functionally relevant changes in the amygdala.…”
Section: Microbiota Modulates Amygdala Structure and Functionsupporting
confidence: 78%
See 2 more Smart Citations
“…Most convincingly, converging evidence from GF mice indicates that the amygdala transcriptome is hyperactive in the absence of a microbiota. [36,37] This hyperactive state is consistent with the altered phenotype of GF mice in regards to both social and fearrelated behaviors, [101,110] pain sensitivity, [119] as well as elevated stress-induced HPA axis responses (see Figure 4). [8,10] More broadly, the studies outlined below suggest that microbiota-toamygdala signalling may result in functionally relevant changes in the amygdala.…”
Section: Microbiota Modulates Amygdala Structure and Functionsupporting
confidence: 78%
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
See 1 more Smart Citation
“…The absence or disruption of gut microbes can significantly influence visceral pain perception, leading to visceral hypersensitivity. In particular, germ‐free mice exhibited increased visceral pain responses when exposed to colorectal distension (CRD) stimuli, and visceral hypersensitivity was normalized after microbial colonization . Furthermore, rats receiving early‐life antibiotic treatment also displayed visceral hypersensitivity in adulthood and altered microbiota profiles .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they showed increased blood-brain barrier permeability [24]. Functionally, such changes translate to increased stress response [14, 16], changes in anxiety [25] and fear recall [26], cognitive deficits [27], social changes [21, 28] and visceral pain responses [29]. Thus, the complete absence of microbial colonization in early life has dramatic effects on offspring’s brain development and function.…”
Section: Early-life Neurodevelopmental Plasticity and The Microbiotamentioning
confidence: 99%